Near infrared electron acceptors with a photoresponse beyond 1000 nm for highly efficient organic solar cells. Issue 35 (24th August 2020) - He, Chengliang; Li, Yaokai; Liu, Yanfeng; Li, Yuhao; Zhou, Guanqing; Li, Shuixing; Zhu, Haiming; Lu, Xinhui; Zhang, Fengling; Li, Chang-Zhi; Chen, Hongzheng
Abstract : Non-fullerene acceptors with photoresponse beyond 1000 nm were synthesized with different thiophene bridges, which influence molecular orientation and thus device performance. Abstract : Developing near infrared (NIR) organic semiconductors is indispensable for promoting the performance of organic solar cells (OSCs), but addressing the trade-off between voltage and current density thus achieving high efficiency with low energy loss is still an urgent challenge. Herein, NIR acceptors (H1, H2 and H3) with a photoresponse beyond 1000 nm were developed by conjugating dithienopyrrolobenzothiadiazole to 2-(5, 6-difluoro-3-oxo-2, 3-dihydro-1 H -inden-1-ylidene)malononitrile via varied alkyl thiophene bridges. It was found that the linear outward chains in thiophene bridges could mitigate both the conformation disorder of H3 and the electronic disorder of the PBDB-T:H3 blends, which could help to form a favorable blend morphology, facilitating highly efficient photoelectric conversion in the resultant OSCs. As a result, devices based on PBDB-T:H3 achieve a high efficiency of 13.75% with a low energy loss of 0.55 eV, which is one of the highest efficiencies and the lowest energy loss among OSCs with an optoelectronic response near 1000 nm. This work provides a new design strategy towards NIR acceptors for efficient OSCs and future exploration of functional optoelectronics.